Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) A Legacy of Excellence and a Vision for the Future - Amy Zulaikha, Mohd Ali (UMPSA, 2023)
This institution was established as Kolej Universiti Kejuruteraan dan Teknologi Malaysia (KUKTEM) in 2002. It then evolved into a fully-fledged university and underwent a transformation, leading to its renaming as Universiti Malaysia Pahang (UMP) in February 2007. Emerging as a guiding light of academic excellence and holistic growth, UMP, commemorating its 21st anniversary in February 2023, is now known as Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA). Named in honour of His Majesty Yang Maha Mulia Seri Paduka Baginda Yang di-Pertuan Agong Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah Ibni Almarhum Sultan Haji Ahmad Shah Al-Musta’in Billah, this institution has etched an indelible mark in the academic realm. It has captured hearts and minds since its rebranding. In the words of the Vice-Chancellor, Professor Dato’ Ts. Dr. Yusserie Zainuddin, the rebranding at the peak of success coincides with the university’s vision towards a leading technological university and will build the university’s visibility, reputation, and capabilities in line with its world-recognised achievements.